2008
DOI: 10.1016/j.resuscitation.2008.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation Outcomes Consortium (ROC) PRIMED cardiac arrest trial methods

Abstract: Aim-The primary aim of this study is to compare survival to hospital discharge with a modified Rankin score (MRS) ≤3 between standard cardiopulmonary resuscitation (CPR) plus an active impedance threshold device (ITD) versus standard CPR plus a sham ITD in patients with out-ofhospital cardiac arrest. Secondary aims are to compare functional status and depression at discharge and at 3 and 6 months post discharge in survivors.Design: Prospective, double-blind, randomized, controlled, clinical trial. Population:P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 31 publications
(29 reference statements)
0
35
0
Order By: Relevance
“…Detailed description of methodology has been given previously. [15,16] PRIMED studied two different resuscitation strategies: thirty-seconds vs. three-minutes of CPR prior to initial rhythm analysis, and an impedance valve vs. sham device during OHCA. [13,14] Research personnel at participating sites prospectively collected patient-level data, including prehospital data streams and audio recordings, from consecutive OHCA subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed description of methodology has been given previously. [15,16] PRIMED studied two different resuscitation strategies: thirty-seconds vs. three-minutes of CPR prior to initial rhythm analysis, and an impedance valve vs. sham device during OHCA. [13,14] Research personnel at participating sites prospectively collected patient-level data, including prehospital data streams and audio recordings, from consecutive OHCA subjects.…”
Section: Methodsmentioning
confidence: 99%
“…The structure, surveillance methodology, and participants of the ROC have been reported elsewhere. 10 In brief, the ROC is a clinical research consortium with 10 sites in the United States and Canada. The ROC conducts population-level regional OHCA surveillance, as well as clinical trials for the prehospital treatment of OHCA and major trauma.…”
Section: Methodsmentioning
confidence: 99%
“…PRIMED was a partial factorial design which tested two interventions: a brief versus longer period of CPR by EMS prior to analysis for defibrillation and assessing the effectiveness of an active vs. sham Impedance Threshold Device (ITD). (10, 11) Neither the CPR strategies nor the ITD device was significantly associated with survival to hospital discharge or functional outcome. (12, 13) Concurrently with PRIMED which recruited from 06/2007 to 03/2009, ROC also completed a real-time CPR feedback trial at selected EMS agencies from three sites which showed no significant difference in outcomes between control and intervention arms.…”
Section: Methodsmentioning
confidence: 99%